2020
DOI: 10.1109/access.2020.2992451
|View full text |Cite
|
Sign up to set email alerts
|

The Deep Convolutional Neural Network for NOx Emission Prediction of a Coal-Fired Boiler

Abstract: This paper presents a methodology for predicting NOx emissions of a coal-fired boiler by using real operation data, coal properties and CNN (Convolutional Neural Network). Two building blocks are carefully designed following the practical guidelines for the light weight CNN architecture design. Furthermore, the building blocks are used to develop the deep CNN-based model for NOx prediction. A comprehensive comparison among different prediction models based on DL (Deep Learning) shows that the proposed deep CNN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 21 publications
0
18
1
Order By: Relevance
“…In this section, a comparative analysis of different DL‐based NO x prediction models was conducted to assess the proposed deep CNN‐based model further. The outlines of these DL‐based models are described as follows: the LSTM‐based model consisting of a single LSTM network, 14 the LSTM‐based model composed of two stacked LSTM networks, 15 the DNN‐based model, 18 and the CNN‐based model 19 . Most of the hyperparameters used in these four models can be found in the original references.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this section, a comparative analysis of different DL‐based NO x prediction models was conducted to assess the proposed deep CNN‐based model further. The outlines of these DL‐based models are described as follows: the LSTM‐based model consisting of a single LSTM network, 14 the LSTM‐based model composed of two stacked LSTM networks, 15 the DNN‐based model, 18 and the CNN‐based model 19 . Most of the hyperparameters used in these four models can be found in the original references.…”
Section: Resultsmentioning
confidence: 99%
“…However, their models' performance was heavily based on the training sets' quality 18 . Li and Hu built NO x prediction models based on the convolutional neural network (CNN) and did a detailed comparative analysis among different CNN‐based NO x prediction models 19 . Their studies suggested that it is a considerable alternative approach to build the NO x prediction model based on CNNs.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have applied LSTM and reported good performance in dynamic NOx prediction (Tan et al (2019); Yang et al (2020); Song et al (2022); Xie et al (2020); Wang et al (2022); Tuttle et al (2021)). Some studies have reported that convolutional neural networks (CNN) accurately predicted emissions of NOx from coal-fired boilers (Li and Hu (2020); Saif-Ul-Allah et al (2022,?)). In addition, deep hybrid neural networks also have been applied to CFB gas emission prediction (Hu et al (2020)).…”
Section: Introductionmentioning
confidence: 99%
“…This method is mainly focused on the NOx emission of the exhaust gas. In this regard, numerous algorithms, including statistical regression (Li et al, 2004;Chunlin Wang et al, 2018), support vector machine (Wei et al, 2013;Zhou et al, 2012;Ahmed et al, 2015;Lv et al, 2013), artificial neural network (ANN) (Chu et al, 2003;Ilamathi et al, 2013;Preeti and Sharad, 2013;Jacob and Tuttll, 2019), and deep learning (Li and Hu, 2020;Yang et al, 2020;Tan et al, 2019;Xie et al, 2020;Kang et al, 2017;Wang et al, 2017) are often used to predict the NOx concentration. Although remarkable achievements have been obtained in this area, the time complexity of support vector machines increases exponentially as the sample size increases.…”
Section: Introductionmentioning
confidence: 99%